ICSE 2002 : 2002 IEEE International Conference on Semiconductor Electronics : proceedings : December 19 -21, 2002, The Gurney Resort Hotel & Residences, Malaysia - IEEE International Conference on Semiconductor Electronics (5th : 2002 : Penang, Malaysia); Burhanuddin Yeop Majlis, editor; Sahbudin Shaari, editor; IEEE Malaysia Section; IEEE Electron Devices Society; Mems Technology; Universiti Kebangsaan Malaysia (Piscataway, NJ : IEEE, 2002)
16